2022
DOI: 10.1021/acs.jafc.2c07073
|View full text |Cite
|
Sign up to set email alerts
|

5-Heptadecylresorcinol Regulates the Metabolism of Thermogenic Fat and Improves the Thermogenic Capacity of Aging Mice via a Sirtuin 3–Adenosine Monophosphate-Activated Protein Kinase Pathway

Abstract: 5-Heptadecylresorcinol (AR-C17), a well-known biomarker for whole grain rye consumption, is a primary homolog of alkylresorcinols. In this study, the effects of AR-C17 on the thermogenesis of brown adipocytes and 3T3-L1 adipocytes were investigated. The results showed that AR-C17 increased sirtuin 3 (Sirt3) expression, and the expressions of specific thermogenic genes in adipocytes were increased. Furthermore, AR-C17 increased the mitochondrial functions during the thermogenic activation of adipocytes. In in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Sirt3 plays a crucial role in the regulation of energy metabolism and can regulate many metabolic processes, such as oxidative phosphorylation, FA oxidation, and the tricarboxylic acid cycle [25]. In our previous study, we showed that AR-C17 improved the metabolism of thermogenic fat and the thermogenic capacity of aged mice via the regulation of Sirt3 [22]. Furthermore, we also revealed that AR-C17 improved the BAT thermogenesis of aged mice via enhancing the acylcarnitine metabolism of BAT [26].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Sirt3 plays a crucial role in the regulation of energy metabolism and can regulate many metabolic processes, such as oxidative phosphorylation, FA oxidation, and the tricarboxylic acid cycle [25]. In our previous study, we showed that AR-C17 improved the metabolism of thermogenic fat and the thermogenic capacity of aged mice via the regulation of Sirt3 [22]. Furthermore, we also revealed that AR-C17 improved the BAT thermogenesis of aged mice via enhancing the acylcarnitine metabolism of BAT [26].…”
Section: Introductionmentioning
confidence: 89%
“…5-Heptadecylresorcinol (AR-C17) is a major active homolog of ARs and has been demonstrated to have various health benefits, including anti-oxidant, anti-obesity, anti-inflammatory, and anti-cancer activities [16][17][18][19]. AR-C17 has been demonstrated to modulate various metabolic processes via regulating Sirtuin 3 (Sirt3) [16,[20][21][22]. Sirt3 is a human Sir2 homologue which translocates into mitochondria under cellular stress [23].…”
Section: Introductionmentioning
confidence: 99%
“…All mice were given one-time oral gavage. The dosage of intragastric administration in mice is based on Zhang et al, 13 in which the dosage of AR-C17 in mice was 250 μg/ kg/day, n = 6. Besides, note that the concentration ratio mentioned above means "Quercetin: AR-C17".…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that AR-C17 can improve cognitive impairment and relieve neuroinflammation in mice . Besides, our previous study demonstrated that AR-C17 is a promising thermogenic activator for adipocytes to relieve metabolic diseases related to obesity and aging . Therefore, AR-C17 has significant potential that deserves further nutrition development.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation